IMPLEMENTASI PERMENDAGRI NOMOR 76 TAHUN 2012 DALAM PENETAPAN DAN PENEGASAN BATAS DESA SECARA KARTOMETRIS - Bambang Riadi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2015)
Delimitation of the village under Regulation No. 27 In 2006 (Permendagri No.27 Tahun 2006) the process of delimitation of the village on a map kartometris on an agreed basis. Implementation of the determination and the assertion made above the village boundary map scale of 1: 5,000 s / d 1: 10.000. Availability best scale topographical map is a scale of 1: 10,000 s / d 1: 25,000 which covers most of the territory of the Republic of Indonesia. The publication of Regulation No. 76 of 2012 as a replacement for the previous Regulation, explains that setting boundaries is kartometris can be done within the framework of demarcation between the regions by using a data base topographical maps. Development of mapping technology allows updating border activities carried out by combining the techniques of Remote Sensing, Geographic Information Systems and Digital Elevation Model (DEM). Determination and demarcation village implemented to provide legal certainty to the village boundaries in the land. Kartometris delimitation of the village is the process of setting boundaries on a map on an agreed basis, the process of implementation in the field by providing a mark in the form of coordinates kartometris village. Registered image data refers to the provisions of the topographical map. Test Results horizontal accuracy CE 90 are: image with GCP field measurement results by 6 points with accuracy 0.098 m; 22 points with accuracy 1.431 m. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i1.1352